What predicts how safe people feel in their neighborhoods and does it depend on functional status? - Alfredo J. Velasquez; Jason A. Douglas; Fangqi Guo; Jennifer W. Robinette (Elsevier, 2021)
Feeling unsafe in one's neighborhood is related to poor health. Features of the neighborhood environment have been suggested to inform perceptions of neighborhood safety. Yet, the relative contribution of these features (e.g., uneven sidewalks, crime, perceived neighborhood physical disorder) on perceived neighborhood safety, particularly among people with disabilities who may view themselves as more vulnerable, is not well understood. We examined whether sidewalk quality assessed by third party raters, county-level crime rates, and perceived neighborhood disorder would relate to neighborhood safety concerns, and whether functional limitations would exacerbate these links. Using data from the 2012/2014 waves of the Health and Retirement Study (n = 10,653, mean age = 66 years), a national sample of older US adults, we demonstrate that those with and without functional limitations felt less safe in areas with more crime and perceived as more disordered. When considered simultaneously, however, only perceived disorder statistically significantly predicted safety concerns. Living in neighborhoods with better sidewalk quality was statistically significantly related to feeling less safe, but only among those with functional limitations. Sidewalk quality was not statistically significantly related to safety reports among those without functional limitations. To our knowledge, this study is among the first to examine multiple features of the neighborhood environment simultaneously in relation to perceived neighborhood safety. Our findings highlight the relative importance of perceived physical disorder, and that these perceptions relate to safety concerns. Replication of this research is needed to determine the robustness of these patterns, including rich data on pedestrian use and sidewalk proximity to roadways. Community-level interventions that simultaneously target the multifaceted features of the neighborhood environment that shape people's safety reports may be needed to reduce burden of health.